2005
DOI: 10.1111/j.1348-0421.2005.tb03672.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Specific Inhibition of Paramyxovirus Maturation by Proteasome Inhibitors

Abstract: Effects of proteasome inhibitors on the replication of a paramyxovirus in comparison with the effects on replication of an orthomyxovirus and rhabdovirus were investigated. Treatment of Sendai virus (SeV)‐infected LLC‐MK2 cells with 50 μM MG132 reduced virus growth to ca. 1/10,000, and treatment with different concentrations of MG132 reduced virus growth in a dose‐dependent manner. Released amounts of viral proteins were reduced in correspondence with decrease in infectivity. The inhibition of virus maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…8). This finding is consistent with several studies that suggested that ubiquitin is involved in viral budding: (i) proteasome inhibitor treatments block the budding of paramyxoviruses, including PIV5, NiV, and SeV (26,31,58); (ii) potential ubiquitination of the MeV M protein has been observed in cells expressing the M protein together with HA-Ub (38); and (iii) ESCRT factors such as ALIX can bind to ubiquitin and enhance viral budding (59,60).…”
Section: Discussionsupporting
confidence: 79%
“…8). This finding is consistent with several studies that suggested that ubiquitin is involved in viral budding: (i) proteasome inhibitor treatments block the budding of paramyxoviruses, including PIV5, NiV, and SeV (26,31,58); (ii) potential ubiquitination of the MeV M protein has been observed in cells expressing the M protein together with HA-Ub (38); and (iii) ESCRT factors such as ALIX can bind to ubiquitin and enhance viral budding (59,60).…”
Section: Discussionsupporting
confidence: 79%
“…To test whether this degradation system could be involved, we treated cells with specific inhibitors and monitored the effect of NSs on PKR. Inhibition of the proteasomal system by MG132 had a negative effect on RVFV growth, similar to what was observed for other RNA viruses (29,49,67). Nonetheless, dose-response experiments using different concentrations show that MG132 partly restored PKR levels in RVFV-infected cells (Fig.…”
Section: Antiviral Effect Of Ifn and Pkr Against Rvfvsupporting
confidence: 49%
“…Therefore, one might suspect that specifically inhibiting the ubiquitin-independent proteasomal degradation events that appear to preferentially target cellular tumor suppressors and viral oncogenes could approach the therapeutic effect of complete proteasome inhibition without invoking as many deleterious side effects. As many viruses are inhibited in vitro by proteasome inhibitors [161-165], curtailing ubiquitin-independent degradation events certainly has therapeutic potential for viral infections. Because PA28γ plays a conspicuous role in many ubiquitin-independent degradation events, modalities that inhibit its expression, function, or prevent it from associating with the 20S CP could provide therapeutically relevant inhibition.…”
Section: Discussionmentioning
confidence: 99%